2019
DOI: 10.1007/s11469-019-00066-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychiatric Risk Factors of Excessive Internet Use among Northern Bangladeshi Job-Seeking Graduate Students: A Pilot Study

Abstract: Although internet addiction (IA) has been the subject of research in many countries, it is poorly studied in Bangladesh, and previous studies in the country have not examined potential mental health risk factors in relation to the development of IA. The present pilot study attempted to assess the prevalence and associated risk factors of IA among a convenience sample of recently graduated university students actively looking for a job (N = 284) from July to October 2018 in Rajshahi (a city in Bangladesh). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 37 publications
6
46
2
Order By: Relevance
“…It has been reported that individuals with PIU have more irregular sleeping patterns and episodes of disturbed sleep than non-problematic internet users (Bener & Bhugra, 2013;Bener et al, 2019). In other studies conducted in Bangladesh, it has also been reported that having more and less sleeping time is a risk factor for IA (Afrin et al, 2017;Islam & Hossin, 2016;Jahan et al, 2019, Mamun & Griffiths, 2019aMamun, Rafi, et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been reported that individuals with PIU have more irregular sleeping patterns and episodes of disturbed sleep than non-problematic internet users (Bener & Bhugra, 2013;Bener et al, 2019). In other studies conducted in Bangladesh, it has also been reported that having more and less sleeping time is a risk factor for IA (Afrin et al, 2017;Islam & Hossin, 2016;Jahan et al, 2019, Mamun & Griffiths, 2019aMamun, Rafi, et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…This is much higher that the rates reported in two previous Bangladeshi studies. In the first study, Mamun, Rafi, et al (2019) reported that 3.9% of their sample of recent graduate job seekers scored ≥60 on the IAT (and also argued that being an active job seeker might be a protective factor because the individuals did not have the time to spend hours a day on the internet because they were actively job-seeking). In the second study by Karim and Nigar (2014) reported that 1.74% university students in their sample scored ≥62 on the IAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the major omissions in the paper is that in their Introduction, not a single previous Bangladeshi study was discussed even though there are many (e.g., [8][9][10][11][12][13][14][15][16][17][18][19][20][21] -see Table 1 for details), and only one was mentioned in the Discussion [10]. Hasan also claimed that: "Most of the studies conducted previously evaluated the prevalence of internet addiction and its predictors in adolescent samples, within the age range of 12 to 18 years" (p. 2).…”
mentioning
confidence: 99%